Virtual Learning Environments in University Faculty Practice Communities of Ecuador - Arroyo Vera, Zoila (2018)
The use of virtual learning environments represents a paradigm shift in the ways in which the university teaching process is carried out. In Ecuador, there is great potential for the use of virtual learning environments in universities; however, most teachers do not know the benefits of the platforms and refuse to use them. The objectives of the study were: 1) to examine theoretical aspects of virtual learning environments in the university context and 2) to identify the characteristics of virtual learning environments in Ecuador. To obtain results, methods were proposed at the theoretical and empirical levels. The characteristics and benefits of virtual learning environments were discussed and the advantages that their intensive use would bring to the community of teachers' practice in Ecuador were analyzed.